2021
DOI: 10.1039/d1cp03103a
|View full text |Cite
|
Sign up to set email alerts
|

Regularized dynamical decoupling noise spectroscopy – a decoherence descriptor for radicals in glassy matrices

Abstract: Decoherence arises from a fluctuating spin environment, captured by its noise spectrum S(ω). Dynamical decoupling (DD) with n π pulses extends the dephasing time if the associated filter function attenuates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…It has been reported that classical rotation of tempone methyl groups gets slow on the ENDOR timescale below 80 K, 54 however, librations in general remain relevant below that temperature. 4 Moreover, the fast decaying contribution, which we attribute to methyl tunneling, 11 is not easily identifiable above 60 K, since the matrix-induced decoherence becomes very fast and a single stretched exponential suffices to fit the decay trace. This trend is also clearly visible in the extracted Gaussian rotation barrier distributions parameterized by V 3,av and σ shown in Fig.…”
Section: Temperature Dependence Of Tunneling Eseemmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that classical rotation of tempone methyl groups gets slow on the ENDOR timescale below 80 K, 54 however, librations in general remain relevant below that temperature. 4 Moreover, the fast decaying contribution, which we attribute to methyl tunneling, 11 is not easily identifiable above 60 K, since the matrix-induced decoherence becomes very fast and a single stretched exponential suffices to fit the decay trace. This trend is also clearly visible in the extracted Gaussian rotation barrier distributions parameterized by V 3,av and σ shown in Fig.…”
Section: Temperature Dependence Of Tunneling Eseemmentioning
confidence: 96%
“…where the matrix-induced decoherence is described by a stretched exponential function with phase memory time T m and stretched exponent ξ , based on assignment of this contribution to the slower of two stretched exponent terms in earlier work. 4,11 In the following we refer to this model as the methyl quantum rotor (MQR) model.…”
Section: Tunneling Eseem In a Glassy Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, each pulse sequence can be seen as a path for a (quasi-)decay of electron coherence due to the nuclei-related dephasing, and at the same time it can be seen as a filter function, selecting certain electron-nuclear frequencies and sup-pressing others. The latter process is often called dynamical decoupling (Soetbeer et al, 2021a). The first interpretation can also be seen as a type of filtering, albeit a different one: local nuclear configurations around electron spins might differ in the characteristic decay times, due to the strengths of the couplings or due to the different statistics of nuclear spinup and spin-down states.…”
Section: Electron-proton Contributions and Transverse Relaxationmentioning
confidence: 99%
“…The molecular structure resembles o-terphenyl (OTP), the model glass-forming liquid, which is the subject of longstanding investigations. [45][46][47][48][49][50][51] OTP is broadly applied as a raw material for organic synthesis and pharmaceutical intermediate, and its derivatives are used in organic light-emitting diodes (OLEDs). [52][53][54] The chemically more complex molecule of DFP25DFT possesses polar groups and alkyl chains in alkoxy moieties that generally act as a trigger of crystallization.…”
Section: Introductionmentioning
confidence: 99%